2010
DOI: 10.1007/s12308-009-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

NK cell lymphoma, nasal type, with massive lung involvement: a case report

Abstract: Extranodal NK/T cell lymphoma, nasal type, is an Epstein-Barr virus-associated lymphoma that most commonly involves the nasal cavity and upper respiratory tract. Lung involvement by NK/T cell lymphoma is rare and seldom reported in the literature. We describe the unusual case of a 41-year-old male with NK cell lymphoma, nasal type, who presented with massive secondary lung involvement 2.5 years after the detection of a retroperitoneal mass. The diagnosis was made by open lung biopsy. Despite aggressive treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Morovic et al reported a case of nasal NK/ T-cell lymphoma with secondary lung involvement, despite aggressive chemotherapy and intensive supportive treatment, the patient died shortly after the initiation of therapy. 31 In conclusion, despite the rarity of NK/T-cell lymphoma it is important for otolaryngologists and ophthalmologists to consider ocular involvement and distant metastases. The present case demonstrates that nasal NK/T-cell lymphoma can occur intraocular and widely disseminate aggressively with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morovic et al reported a case of nasal NK/ T-cell lymphoma with secondary lung involvement, despite aggressive chemotherapy and intensive supportive treatment, the patient died shortly after the initiation of therapy. 31 In conclusion, despite the rarity of NK/T-cell lymphoma it is important for otolaryngologists and ophthalmologists to consider ocular involvement and distant metastases. The present case demonstrates that nasal NK/T-cell lymphoma can occur intraocular and widely disseminate aggressively with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Morovic et al reported a case of nasal NK/T-cell lymphoma with secondary lung involvement, despite aggressive chemotherapy and intensive supportive treatment, the patient died shortly after the initiation of therapy. 31…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search for case reports since 2000 using the keywords "primary pulmonary NK/T-cell lymphoma" yielded 18 case reports written in English (case reports written in Chinese were excluded) (Table 2) [8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can also occur at extranasal sites (the skin, liver, spleen, gastrointestinal tract, bone marrow, lung, and so on). A primary presentation of ENKTCL in the lung and ENKTCL involving only the lung is rare ( 1 2 ). Furthermore, there is no report which primary pulmonary ENKTCL is presented with ground glass opacities (GGOs).…”
Section: Introductionmentioning
confidence: 99%